Responsivitas Pemerintah Daerah Dalam Pemulihan Pencemaran Limbah Cair Industri Di Sungai Citarum: Studi Pada Dinas Lingkungan Hidup Dan Kebersihan Kabupaten Karawang - Mutiara Elvina Sairin; Haura Atthahara; Dadan Kurniansyah (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study discusses the responsiveness of local governments in recovering industrial wastewater pollution in the Citarum River: with the focus of the study on the Department of Environment and Hygiene, Karawang Regency. This research will be discussed using the theory of responsiveness from (Igor Ansof and E. McDonneell, 1990) with three dimensions in it, namely Climate (Will to Respond), Competence (Ability To Respond), and Capacity (Volume of Response). This research uses a descriptive case study with a qualitative approach. Data collection techniques are carried out by means of observation, interviews, documentation, and combination/tigulation, then the data is analyzed interactively and continues until it is complete, so that the data is saturated. Data analysis activities are data reduction, data display, conclusion drawing/verification. The results of the discussion show that the strength is in the policies made, and the power and influence from the non-government side. The structure has established good relations and good coordination between the Environment Agency and PT. Pindo Deli especially in the recovery of industrial wastewater pollution. Culture there are two different statements, when the informant PT. Pindo Deli, who said that the inspections carried out by the Environmental Service were uncertain and could even be counted within one year, only 1-2 times.